2020
DOI: 10.1002/best.202000048
|View full text |Cite
|
Sign up to set email alerts
|

Instandsetzung von gefugten Betonflächen mit einer dünnen Schicht aus Carbonbeton

Abstract: Ein typisches Anwendungsfeld für gefugte Betonflächen sind Betonfahrbahnen. Diese sind hohen Beanspruchungen aus dem Verkehrsaufkommen und extremen Witterungsbedingungen ausgesetzt. Um wilde Risse aus daraus entstehenden Zwangsspannungen zu verhindern, werden in der Regel Querscheinfugen eingebracht. Diese stellen jedoch zugleich eine Schwachstelle im Beton dar, sodass eine kontinuierliche Instandhaltung und Wartung notwendig werden. Eine ökologisch und ökonomisch sinnvolle Alternative zur Erneuerung der gesam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Depending on the type of failure, a significant level of strengthening was achieved 15 . Further investigations showed that TRC layers can be realized for strongly exposed components without additional sealing or road surfaces 16,17 …”
Section: Rehabilitation Of Road Surface Using Textile‐reinforced Conc...mentioning
confidence: 99%
“…Depending on the type of failure, a significant level of strengthening was achieved 15 . Further investigations showed that TRC layers can be realized for strongly exposed components without additional sealing or road surfaces 16,17 …”
Section: Rehabilitation Of Road Surface Using Textile‐reinforced Conc...mentioning
confidence: 99%
“…39 The mathematically described and averaged bond stress-slip curve is then used for the calculation of the required anchorage length and to predict the crack widths and spacing for a given load, see Reference [9]. Besides the calculation algorithms presented in Reference [9], other models for the calculation of crack widths are known, for example, as presented in [Reference 40] Since the calculation algorithms from Reference [9] are based on SPO tests, they were used for the research in the presented project and adapted for the special application. By creating an extensive tool using Microsoft Excel software to analyze the data of a high number of specimens, it was possible to define a multilinear bond-slip relation.…”
Section: Bond-slip Relation and Calculation Of Crack Formationmentioning
confidence: 99%
“…In the SPO tests, a correlation between the force and the crack opening is determined which can be converted into a bond stress‐slip relation, using simplified formulas 38 or other numerical methods 39 . The mathematically described and averaged bond stress‐slip curve is then used for the calculation of the required anchorage length and to predict the crack widths and spacing for a given load, see Reference [9]. Besides the calculation algorithms presented in Reference [9], other models for the calculation of crack widths are known, for example, as presented in [Reference 40] Since the calculation algorithms from Reference [9] are based on SPO tests, they were used for the research in the presented project and adapted for the special application.…”
Section: Experimental Investigation Of Crack Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 9. Example of the change of the relative dynamicYoung's modulus on beams with cracks considered for the CRC layer; adapted from[20] …”
mentioning
confidence: 99%